NIR‐triggered hydrogel with dynamic stiffness via ion chelation to modulate macrophage phenotypes. Issue 23 (8th August 2022) - Yuan, Peiqi; Luo, Yilun; Ma, Lie
Abstract: The immune system plays a central role in tissue repair and regeneration. Macrophages have emerged as a primary target because of their critical roles in regulating multiple phases of tissue repair through their unique plasticity and ability to rapidly shift phenotypes. Smart biomaterials, which able to harness macrophage phenotypes on demand during the healing process, have become a promising strategy. Here, a novel integrated hydrogel with near‐infrared (NIR) responsive dynamic stiffness was conducted, and found sequentially polarizing bone marrow‐derived macrophages from pro‐inflammatory to anti‐inflammatory phenotype in situ. Under NIR irradiation, ethylene diamine tetraacetic acid released from the IR780‐mixed phase change material into the hydrogel, resulting in the decrease of hydrogel stiffness in situ by chelating the calcium ion (Ca 2+ ) in the calcium alginate hydrogel. The up‐regulation of arginase‐1 and interleukin‐10 were quantified by immunostaining and enzyme‐linked immune sorbent assay, respectively. The result indicated the transformation of macrophage from the pro‐inflammatory to anti‐inflammatory phenotype by dynamic stiffness drop. The modulation of macrophage phenotypes by stiffness‐degradation without the stimuli of cytokines offers an effective and noninvasive strategy to manipulate inflammatory or tissue‐regenerative immune responses to achieve optimized healing or therapeutical outcomes. Abstract :